Impacts of heavy smoking and alcohol consumption on workplace presenteeism: A cross-sectional study. Issue 47 (24th November 2021) - Lee, So Young; Lee, Jinhwa; Kwon, Min
Abstract : Abstract: Presenteeism refers to the practice of going to work despite poor health, resulting in subpar performance. This study aimed to explore the impacts of smoking and alcohol consumption on workplace presenteeism based on demographic, health-related, and employment variables. The study adopted a cross sectional design with 60, 051 wage workers from the database of the second and third Korean Working Conditions Surveys in 2010 and 2011, respectively. A total of 41, 404 workers aged 19 years and older, who had worked for at least 1 hour in the previous week, answered the survey questions. Chi-square test as well as univariate and multiple logistic regression analyses were conducted using SPSS, version 18.0, to determine the impacts of smoking and alcohol consumption on workplace presenteeism. Of the 41, 404 Korean workers, 8512 (20.6%) had experienced presenteeism in the past 12 months. There were significant differences among gender, age, educational status, income, health problems, absenteeism, shift work, night shift, weekly working hours, exposure to secondhand smoke at work, and satisfaction with the workplace environment. Based on the results of multiple regression analysis, heavy smoking (adjusted odds ratio = 1.38, 95% confidence intervals [1.11, 1.72]) and high-risk drinking (adjusted odds ratio = 1.19, 95% confidence intervals [1.08, 1.31]) were significantly related to presenteeism among workers. The results of our study confirmed that smoking and alcohol drinking were related to presenteeism even after controlling other variables (demographic, health-related, and employment variables) that affect presenteeism. Smoking and alcohol drinking are associated with and potentially influence presenteeism; in particular, heavy smoking and high-risk drinking contributed to presenteeism. Companies that encourage employees to receive treatments for reduction of smoking or alcohol consumption may benefit from greater productivity. Hence, we should consider the impact of smoking and alcohol consumption in the workplace and build appropriate strategies and programs to help reduce these behaviors. Abstract : Supplemental Digital Content is available in the text